2016
DOI: 10.1016/j.tcs.2015.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Order-preserving indexing

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 39 publications
(55 reference statements)
2
27
0
1
Order By: Relevance
“…For the offline problem, Crochemore et al showed how, given a sequence T [1, n ], in scriptOfalse(nlogfalse(nfalse)false/loglognfalse) time, we can build an scriptOfalse(nlognfalse)‐bit index such that, later, given a pattern P [1, p ], we can return the starting positions of all the occ order‐preserving matches of P in T in optimal scriptOfalse(m+sans-serifoccfalse) Time. A more space‐economical solution is proposed by Gagie et al consisting of an index taking scriptOfalse(nloglognfalse) extra bits in addition to the text.…”
Section: Problem Formulation and Previous Resultsmentioning
confidence: 99%
“…For the offline problem, Crochemore et al showed how, given a sequence T [1, n ], in scriptOfalse(nlogfalse(nfalse)false/loglognfalse) time, we can build an scriptOfalse(nlognfalse)‐bit index such that, later, given a pattern P [1, p ], we can return the starting positions of all the occ order‐preserving matches of P in T in optimal scriptOfalse(m+sans-serifoccfalse) Time. A more space‐economical solution is proposed by Gagie et al consisting of an index taking scriptOfalse(nloglognfalse) extra bits in addition to the text.…”
Section: Problem Formulation and Previous Resultsmentioning
confidence: 99%
“…Let us start by recalling the encoding for op-pattern matching (op-encoding) from [19,37]. For a string S of length n and i ∈ 1..n we define:…”
Section: Algorithmic Toolbox For Op-modelmentioning
confidence: 99%
“….n] such that op-PREF[i] is the length of the longest prefix of S[i..n] that is equivalent to a prefix of S. It is a direct analogue of the PREF array used in standard string matching (see [21]) and can be computed similarly in O(n) time using one of the standard encodings for the op-model that were used in [15,19,37]; see lemma below.…”
Section: Op-pref Tablementioning
confidence: 99%
See 2 more Smart Citations